2008
DOI: 10.4049/jimmunol.180.9.5771
|View full text |Cite
|
Sign up to set email alerts
|

IL-10: The Master Regulator of Immunity to Infection

Abstract: IL-10 is an anti-inflammatory cytokine. During infection it inhibits the activity of Th1 cells, NK cells, and macrophages, all of which are required for optimal pathogen clearance but also contribute to tissue damage. In consequence, IL-10 can both impede pathogen clearance and ameliorate immunopathology. Many different types of cells can produce IL-10, with the major source of IL-10 varying in different tissues or during acute or chronic stages of the same infection. The priming of these various IL-10-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,520
9
38

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,919 publications
(1,618 citation statements)
references
References 97 publications
51
1,520
9
38
Order By: Relevance
“…IL-12 is considered a link between innate and adaptive immunity (48,49), and may be related to the pathogenesis of periodontal disease (50)(51)(52). Another interesting observation in the present study is that the production of the anti-inflammatory cytokine IL-10 was increased in response to LDD, possibly potentiating its beneficial effects to the host (53). This is an important finding as the relative IL-1beta/IL-10 ratio has been shown to be higher in aggressive periodontitis patients than periodontally healthy subjects (54).…”
Section: Actinomycetemcomitans Lps (42) In Other Experimental Systemsupporting
confidence: 51%
“…IL-12 is considered a link between innate and adaptive immunity (48,49), and may be related to the pathogenesis of periodontal disease (50)(51)(52). Another interesting observation in the present study is that the production of the anti-inflammatory cytokine IL-10 was increased in response to LDD, possibly potentiating its beneficial effects to the host (53). This is an important finding as the relative IL-1beta/IL-10 ratio has been shown to be higher in aggressive periodontitis patients than periodontally healthy subjects (54).…”
Section: Actinomycetemcomitans Lps (42) In Other Experimental Systemsupporting
confidence: 51%
“…The majority of IL‐10 is produced by macrophages and dendritic cells and with lessor amounts produced by T and B cells47 including B1a cells 5, 8. Consistent with these reports, we found that RMT1‐10 treatment increases IL‐10‐expressing B1a cells without affecting plasma IL‐10 levels.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to tumor-associated regulatory responses, B cells showed a dramatic decrease in IL-10 production compared to controls (Figure 4f). 20 As in allergic responses we also found an intense eosinophil infiltration in the tumor microenvironment of IL-33 treated mice (Figure 4g). 21 Taken together, these data suggest that direct peritoneal delivery of IL-33 can mediate an allergic-like CD4 T-cell activation and expansion, which mediates eosinophil recruitment and promotes uniquely B-cell activation with predominant class switching into IgE and decrease in production of IL-10.
10.1080/2162402X.2018.1515058-F0004Figure 4.IL-33 promotes peritoneal CD4 T-cell and B cell activation and eosinophil recruitment. (A) Real-time quantitative-PCR of IL-5 expression in CD4 + T-cells sorted from the peritoneal cavity of mice bearing intraperitoneal ID8- Defb29/Vegf-a syngeneic tumors treated intraperitoneally with IL-33 or PBS (triplicates, pooled from 5 mice per group, 2 independent experiments).
…”
Section: Resultssupporting
confidence: 54%